Melanoma and medical education: knowledge and sun safety practices amongst medical students - Nicolina Smith; Margaret Finn; Larry Segars; Erin Burns; Johanna Peterson; Angela Sutton; Kaitlin Vogt; Molly Menser (Our Dermatology Online, 2018)
Introduction: Melanoma has become a public health problem; however, with proper education and the use of sun safety techniques, most cases can be prevented. The purpose of this study is to determine if medical students have safer sun practices than the general population. Material and Methods: An online survey was sent to all students enrolled in the three medical schools in the Kansas City metropolitan area. Surveys were sent to 1200 medical students with a 39.25% response rate (n=471). Results: Most of the student population (n=436; 92.6%) indicated that over the past year they had used one or more forms of sun protection. Of the respondents, 60.7% (n=286) indicated they had, to this point in their medical training, been educated counseling patients about the risk factors for prevention of skin cancer. Respondents who indicated that they had been educated on the steps/procedures of a complete skin exam were significantly more likely to indicate they had used sun protective equipment in the past year (P=.024). Conclusions: The general population is in need of dermatologic education on the basic risk factors of skin cancer as well as ways to prevent skin cancer. As education increases in the general population one would anticipate that these individuals would engage in safe sun practices as seen in the medical student community.